2010
DOI: 10.1590/s1980-65232010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of second primary oral cancer tumors: a retrospective study

Abstract: Purpose: Most head and neck malignant neoplasias are diagnosed in advanced stages. Another threatening element to the patients' survival chances and quality of life is the high risk of developing a second primary tumor (SPT). SPT significantly worsens prognosis, and for that reason patients must be monitored for early diagnosis. The main objective of this study was to analyze the occurrence of SPTs in patients with oral squamous cell carcinoma (OSCC) treated in Erasto Gaertner Hospital (EGH), Curitiba, PR, Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The average interval between diagnosis of first primary tumour and SPN was 65 months. 14 Rajani et al in their study on a group of Indian people showed the most common subsites of oral cancer leading to SPN were lower gingivobuccal sulcus followed by palate, tongue and buccal mucosa. 15 Hoarseness of voice is a usual presenting feature of early stage glottic carcinoma while dysphagia and aspiration present late in the course.…”
Section: Discussionmentioning
confidence: 98%
“…The average interval between diagnosis of first primary tumour and SPN was 65 months. 14 Rajani et al in their study on a group of Indian people showed the most common subsites of oral cancer leading to SPN were lower gingivobuccal sulcus followed by palate, tongue and buccal mucosa. 15 Hoarseness of voice is a usual presenting feature of early stage glottic carcinoma while dysphagia and aspiration present late in the course.…”
Section: Discussionmentioning
confidence: 98%